The value of Gissane's angle in the population of Central Serbia - Kovačević, Milan; Banković, Ivona; Aksić, Milan; Rakić, Jovan; Radunović, Aleksandar; Vulović, Maja (Vojnosanitetski pregled, 2022)
Background/Aim. Determining the value of Gissane’s angle (GA) plays a role in the diagnosis and prognosis of heel fractures, determining treatment methods, and assessing the outcome of surgical treatment. Normal values of the GA vary in relation to ethnicity, age, and gender of the examined group, which indicates its anthropometric significance. The aim of this study was to determine the range of normal GA values in the population of Central Serbia. Methods. GA was determined on lateral radiography of the foot of 145 subjects of both sexes (67 women and 78 men), with subjects divided into 6 age groups. The patients included in the study did not have a calcaneus fracture. The obtained results were processed in the Graph Pad program. Results. The average value of GA in Central Serbia was 110.8° ± 8.1°, ranging from 93° to 132.9°. The mean value of GA decreased with age, and no difference was observed between women and men, except in the youngest age group, where women had higher GA values than men. Conclusion. The results of the study showed a wide range of normal GA values, as well as the existence of a difference in subjects of different ages and sex.
Keywords: anthropometry; calcaneus; fractures, bone; heel; radiography; sex factors; serbia